Advancing Polymer Composites with MXenes: A Review of Innovations, Characteristics, and Applications - Abubakar, Abdullahi Musa; Yan, Kezhen; Huang, Junxian; Demirelli, Kadir (Taylor & Francis Inc, 2026)
The pursuit of multifunctional performance is reshaping how next-generation materials are designed. Among the most promising contenders are polymer composites enhanced with two-dimensional (2D) nanomaterials. This review focuses on the rapid progress of MXene-based polymer composites, where MXenes, a family of 2D transition-metal carbides, nitrides, and carbonitrides, offer outstanding electrical conductivity, mechanical robustness, and tunable surface chemistry. We summarize current approaches for synthesizing and modifying MXenes, and examine how their interaction with polymers such as polyvinyl alcohol (PVA), polypyrrole (PPy), and polyvinylidene fluoride (PVDF) dictates the resulting structure - property relationships. Particular attention is given to synergistic improvements in strength, electrical and thermal transport, and barrier characteristics. Beyond conventional uses in energy storage and electromagnetic shielding, emerging applications point to energy-harvesting and self-powered platforms. MXene-based composites are now being integrated into triboelectric nanogenerators (TENGs) and hybrid systems employing lead-free piezoelectric or insulating 2D fillers like hexagonal boron nitride, producing flexible, high-output devices. These materials are expanding into biocompatible and even edible electronics for healthcare monitoring and adaptive sensors for environmental or human-machine interfaces, often linked with machine-learning analytics. The review concludes by identifying key challenges - scalable synthesis, long-term stability, and uniform dispersion - and proposing strategies to realize intelligent, durable, and self-sustaining composite technologies.
Keywords: Advanced composite materials; electrical conductivity; energy storage; mechanical strength; Mxenes; polymer composites; Polymer/Mxene composites